UPAYA MENINGKATKAN HASIL BELAJAR IPA PADA KONSEP SISTEM PENCERNAAN MAKANAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS VIIIC SMPN 2 JEMBER TAHUN AJARAN 2019/2020 - Ani Sulistiyawati Ramli (saintifika, 2020)
A cooperative model learning strategy of STAD (Student Teams Achievement Divisions) is a learning model through a cooperatives learning approach that emphasizes on activities and interactions between students to motivate and assist with learning materials to achieve maximum achievement. The purpose of this research was an increase the result of the 8th grade students science study of SMPN 2 Jember. This research method was a qualitative approach. This kind of research was class action research. The class action in this study was done with 2 cycles. The results were by taking a research subject of 8th grade students of SMPN 2 Jember. From tests for study results on cycle one gets an average of 68,75% become 75,50% while on cycle two is average 75,50% become 87,25%. From the rise in average value, the use of STAD (Student Teams Achievement Divisions) cooperative learning methods increases the students learning result to science lessons